Respuesta :

1)

• 6x -2(x -5) = -2 . . . . given

• 6x -2x +10 = -2 . . . . X Cameron errored here. When multiplying -2 by -5, the result is 10, not -10.

• 4x +10 = -2 . . . . . . x terms are correctly collected

• 4x +10 -10 = -2 -10 . . . . add the opposite of the constant on the left

• 4x/4 = -12/4 . . . . divide by the x-coefficient

• x = -3 . . . . . . . . . . simplify

2)

11x -10 = -34 . . . . combine like terms

11x -10 +10 = 34 +10 . . . . addition property of equality

11x = 44 . . . . . . . . simplify

11x/11 = 44/11 . . . division property of equality

x = 4 . . . . . . . . . . . simplify